Regional biotechnology regulations: Design options and implications for good governance - Birner, Regina; Linacre, Nicholas A. (International Food Policy Research Institute, 2008)
Many developing countries are currently in the process of designing regulatory systems that should allow them to use genetically modified organisms (GMOs) for agricultural development, while also managing the food safety and environmental risks potentially associated with these technologies. Various regions of the developing world are seeking to establish regional systems of biotechnology regulation. However, considerable costs are associated with biotechnology regulation, and biosafety specialists are scarce. In addition, there is no consistent understanding of how regional systems of biotechnology regulation can be designed to be effective and efficient, while also fulfilling the principles of good governance, such as transparency, voice and accountability, control of corruption, and avoidance of special interest capture. There are a wide variety of possible regional approaches, differing with regard to the level of centralization, the scope of the regional system, the types of regional institutions and processes, and the types of financing mechanisms. Here, based on findings in the fields of environmental and fiscal federalism and transaction costs economics, we develop a conceptual framework for the assessment of regional systems of biotechnology regulation. The framework specifies design options and assessment criteria, and identifies major trade-offs and their mediating factors. We use the case of West Africa to illustrate this framework, and refer to the European Union for comparison. Our analysis indicates that involving regional experts, stakeholders and policy-makers in the design of a regional regulatory system will help fill knowledge gaps and generate conclusions regarding the trade-offs involved in regional biotechnology regulation.